Changes in Lithium Levels in Bees and Their Products Following Anti-Varroa Treatment - Éva Kolics; Zsófi Sajtos; Kinga Mátyás; Kinga Szepesi; Izabella Solti; Gyöngyi Németh; János Taller; Edina Baranyai; András Specziár; Balázs Kolics (Insects, 2021)
The biggest threat to beekeeping is varroosis caused by the mite Varroa destructor. Chemicals available to treat this fatal disease may present problems of resistance or inconsistent efficacy. Recently, lithium chloride has appeared as a potential alternative. To date, the amount of residue lithium treatments may leave in honeybee products is poorly understood. Honeybees were fed with 25 mM lithiated sugar syrup, which was used in earlier studies. The accumulation and elimination of the lithium were monitored in bees and their products for 22 days. Lithium concentration increased in the entire body of the bees to day 4 post-treatment and then recovered rapidly to the control level. Lithium exposure was found to affect uncapped honey in the short term (<16 days), but ripe (capped) honey measured at the end of the trial remained affected. On the other hand, lithium treatment left beeswax lithium-free. Based on these data, we propose that comprehensive research on harvested honey is needed to decide on the veterinary use of lithium.